Fatores preditivos de progressão da doença renal crônica em umacoorte de crianças e adolescentes em tratamento conservador: desenvolvimento de um modelo clínico preditivo de risco - Debora da Cruz Cerqueira (2012)
Objective: This retrospective cohort study was observational longitudinal carried out in order to develop a model to predict risk for CKD terminal using demographic, clinical and laboratory features of children and adolescents with CKD (stage II to IV) treated at the Interdisciplinary Program Reference CKD on conservative treatment. Patients and Methods: The study included 147 patients aged 0-19 years admitted to the program between 1990 to 2008. The variables analyzed were: age be admitted to the program, primary renal disease (uropathies, glomerulonephritis, cystic disease and others), gender, ethnicity, glomerular filtration rate, proteinuria, blood pressure, hematuria, serum calcium, phosphorus, parathyroid hormone , height z score, albumin,hemoglobin, pH and bicarbonate. The outcome variable was the progression to CKD terminal. Survival analysis was used to assess the time until the occurrence of an event of interest. We have developed a predictive model for the development of CKD terminal. For this, we used the model of failure rates and the Cox proportional statistical C. Finally, we developed a prognostic risk score, using each variable related to CKD. Results: The median renal survival was estimated 98.7 months (95% CI = 68.7 to 129.6). The probability to reach CKD stage 5 was estimated 8% at 1 year, 12% at 2 years, 28% at 5 years and 52% in 10 years. At the end of follow-up, 72 patients (49%) reached stage 5 CKD. In multivariate analysis, three variables remained independentlyassociated with a progression of CKD to end stage: serum creatinine on admission (hazard ratio, HR 2.067, 95% CI = 1.620 to 2.628, P <0.001), severe proteinuria (HR, 2.825 , 95% CI, 1.184 to 6.744, P = 0.019) and nephropathy as primary renal disease (HR 2.318, 95% CI, 1.008 to 5.327, P = 0.048). Thus, it was assigned a risk score for each of the 147 patients. This score ranged from 0 to individual patients without riskfactors and serum creatinine <1.11 mg / dl to 26.5 for those patients with all risk factors on admission and serum creatinine> 2.54 mg / dl. Thus was constructed a risk score, stratifying patients into three categories: low risk (0-3), medium risk (3.1 to 9) and high risk (9.1 to 26.5). The estimated median renal survival for the group of high, mediumand low risk were respectively 24 months (95% CI = 13.6 to 34.9), 89.4 months (95% CI = 69.0 to 109.7) and 181.5 (95% CI = 123.6 to 239.3). The accuracy of the model was considered good by the c statistic, with an area under the curve of 0.84 (95% CI = 0.77 - 0, 92). Conclusion: This study proposes a model to predict risk of progression of CKD throughtests that are routinely requested in individual outpatient visits in children and adolescents at any stage of CKD in which they are providing a better behavior in case of need for therapy renal replacement.